Menilai Kecenderungan Nilai Antar Mata Pelajaran Menggunakan Association Rule Pada Rapidminer - Adi Nurrachman; Muhammad Faisal; Fachrul Kurniawan (Universitas Muhammadiyah Ponorogo, 2021)
The focus of this research is trying to assess the tendency of scores between subjects using the association rule method using Rapidminer. The Association Rule method itself is often called Market Basket Analysis. The results showed that there was a tendency that students with good grades in English had good Mathematics scores with a 100% confidence level with a support value of 0.333